Identifikasi Kebutuhan Ruang Kerja di Kantor Sewa Bisnis Pemula Biro Arsitektur - Mukhtar, Mufliha; Dwiyanto, Agung (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2024)
Architecture firms in Makassar City are generally dominated by entities that do not yet have a physical office to reflect their professionalism and credibility. In the context of the city's rapid growth, the need for an office that demonstrates professionalism becomes increasingly crucial. Rental offices are one of the solutions for architectural firms that do not yet have a representative physical office. Still, currently, the rental offices available in Makassar City cannot meet this need, despite its importance. Meanwhile, there are no standardized criteria for the type and size of space requirements of architectural bureau start-ups' rental offices, so research is needed to identify the necessary number of space units and the most dominant space requirements for architectural bureau start-ups in Makassar City. This research aims to identify how many space units and what space needs are most dominantly needed by a beginner architectural bureau. A mixed research method through literature review and questionnaires was used to gain a holistic understanding. The results showed that the priority space required by a start-up architecture firm with a capacity of less than ten people and an area of approximately 34.25 m2 includes a director's room, administrative staff room, principal architect room, and studio room. At the same time, other needs are still considered in the rental office design as shared facilities.